Shifting Traditional Values Teaching Sasak Tribe Community from Maqashid Asy-Syari'ah Perspective - Anam, Ahmad Gautsul (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
The tradition of memulang is a tradition carried out by the Sasak People as part of the wedding process. In carrying on this tradition, a young man took away his bride without any of the family knowing about it. Focus of this research is (1) what are the factors behind the shift values that occur in the marriage process (2) what is the analiyze of the shift in values toward the memulang tradition to Sasak People in an acculturation perspective and Maqhasid Syari’ah in Gondang Village, Gangga District, North Lombok Regency. This research is a type of qualitative research. Collecting data by interviews, observation as primary data and secondary data obtained from several literatures related to acculturation and Maqhasid Syari’ah. The result showed that : the shift that occurred in this tradition of memulang was due to the modernity of the times caused by the existence of technology, development of education and the existence of apathy in Sasak tribe itself. for Maqhasid Syari’ah, this tradition is believe to be able to cause benefits that occur  including stregthen the bond of the marriage, streghten nasab and streghten persemendaan, so that this perspective can be used as a punishment for memulang tradition.